Highway constructions on the Qinghai-Tibet Plateau: Challenge, research and practice - Aimin Sha; Biao Ma; Hainian Wang; Liqun Hu; Xuesong Mao; Xilan Zhi; Huaxin Chen; Yu Liu; Feng Ma; Zhuangzhuang Liu; Rui He; Wei Si; et al. (Journal of Road Engineering, 2022)
Summary: Highway constructions on the Qinghai-Tibet Plateau (QTP) face great challenges induced by the unique local environmental, geological, and engineering conditions. The large area of permafrost, great temperature variability, strong UV rays, and complex geological conditions are the major factors that adversely influence the long-term performance of pavement systems. Since 1960s, Chinese engineers and researchers have started conducting research on the QTP to enhance the performance and durability of pavement systems. The present paper provide a comprehensive review of challenge, research and practice of highway constructions on the QTP including the special environmental and geological conditions, history of highway constructions on the QTP, major challenges and the state-of-the-art technology of subgrade constructions on permafrost, developments of the pavement structures and materials, performance prediction and maintenance methods of pavement surfaces, and applications of the research achievements on the first expressway on the QTP (i.e., Gongyu Expressway). Based on the comprehensive literature review, it can be found that (1) frost heave and thaw weakening induced subgrade disease and longitudinal cracks on the pavement surface are complex coupled water-thermal-load problems. Engineering solutions are focusing on active cooling and thermal insulation methods, which can help to reduce temperature variations in the subgrade and thus improving its stability, (2) the harsh environmental and construction conditions may reduce the early strength and induce premature damage of cement-treated base materials. Some field validations showed that geocell-reinforced or asphalt-treated flexible base materials can provide better long-term performance, (3) the large temperature variability and strong UV rays can significantly accelerate aging of asphalt binders and greatly reduce the service life of asphalt mixtures. Various binder modification methods were developed for improving their viscoelasticity and enhance the low-temperature cracking resistance of pavement surface materials but are still lack of field validation data and comparisons of their life cycle costs. Therefore, it is recommended that a demonstration research project build test sections to examine a range of pavement structures and materials, and compare their long-term performance and life cycle costs, which can serve as important reference for future highway constructions on the QTP.